Trauma exposure acutely alters neural function during Pavlovian fear conditioning. (December 2018) - Harnett, Nathaniel G.; Ference, Edward W.; Wood, Kimberly H.; Wheelock, Muriah D.; Knight, Amy J.; Knight, David C.
Abstract: Posttraumatic stress disorder (PTSD) is associated with dysfunction of the neural circuitry that supports fear learning and memory processes. However, much of what is known about neural dysfunction in PTSD is based on research in chronic PTSD populations. Less is known about neural function that supports fear learning acutely following trauma exposure. Determining the acute effects of trauma exposure on brain function would provide new insight into the neural processes that mediate the cognitive-affective dysfunction associated with PTSD. Therefore, the present study investigated neural activity that supports fear learning and memory processes in recently Trauma-Exposed (TE) and Non-Trauma-Exposed (NTE) participants. Participants completed a Pavlovian fear conditioning procedure during functional magnetic resonance imaging (fMRI). During fMRI, participants' threat expectancy was continuously monitored. NTE participants showed greater threat expectancy during warning than safety cues, while no difference was observed in the TE group. This finding suggests TE participants overgeneralized the fear association to the safety cue. Further, only the TE group showed a negative relationship between fMRI signal responses within dorsomedial prefrontal cortex (PFC) and threat expectancy during safety cues. These results suggest the dorsomedial PFC mediates overgeneralization of learned fear as an acute result of trauma exposure. Finally, neural activity within the PFC and inferior parietal lobule showed a negative relationship with PTSD symptom severity assessed three months posttrauma. Thus, neural activity measured acutely following trauma exposure predicted future PTSD symptom severity. The present findings elucidate the acute effects of trauma exposure on cognitive-affective function and provide new insight into the neural mechanisms of PTSD.